Quantitation of Mycophenolic Acid and Mycophenolic Acid Glucuronide in Serum or Plasma by LC‐MS/MS. Issue 4 (11th April 2023) - Garg, Uttam; Munar, Ada; Frazee, Clinton
Abstract: Mycophenolic acid (MPA) is an immunosuppressant that is used as an adjunct therapy in renal, liver, and heart transplantation. Due to its narrow therapeutic range, monitoring MPA levels is essential to avoid toxicity and organ rejection. Although immunoassays are available for the determination of MPA, mass spectrometry methods are preferred due to their higher specificity. Herein, we describe a liquid chromatography tandem mass spectrometry (LC‐MS/MS) method utilizing positive ionization electrospray and multiple reaction monitoring (MRM) for the quantification of MPA levels and its conjugate, MPA glucuronide (MPAG). Blood collected in a plain, EDTA, or heparin‐containing tube is centrifuged to separate the serum or plasma. Proteins are precipitated using a zinc sulfate solution and acetonitrile containing deuterated internal standards (MPA‐d3 and MPAG‐d3). The resulting protein‐free supernatant is injected into the LC‐MS/MS system for analysis. The chromatography involves the use of a C18 column and ammonium acetate/water/formic acid and ammonium acetate/methanol/formic acid mobile phases. Quantification of MPA and MPAG levels is achieved by comparing the MRM peak area ratios of analytes and internal standards, consisting of specific precursor/product pairs, with those of calibrators at various concentrations. Calibration curves are constructed from the MRM peak area ratios of calibrators and internal standards versus concentration. © 2023 Wiley Periodicals LLC. Basic Protocol : Quantitation of mycophenolic acid and mycophenolic acid glucuronide in serum or plasma by LC‐MS/MS